The Implementation of the Merdeka Curriculum in Early Childhood Education at Bulukerto Nature Play Group - Rita Hastuti; Syarifan Nurjan; Azam Muttaqin (STAI Terpadu Yogyakarta, 2025)
This study aims to examine the implementation of the Merdeka Curriculum in early childhood education at the Alam Bulukerto Playgroup, which prioritizes the development of creativity and independence through nature-based learning experiences. The Merdeka Curriculum offers flexibility for teachers to tailor learning to each child's unique needs, which is crucial at an early age. This research employs a qualitative descriptive approach with a case study method, where data was collected through direct observation, interviews with teachers, and documentation of activities. The study results indicate that the application of the Merdeka Curriculum in a nature-based play environment encourages exploration and direct interaction with nature, fostering children's self-confidence and interest in the learning process. Activities such as gardening and introducing the local ecosystem help children develop social skills, independence, and critical thinking through real experiences. Children are also more engaged and motivated as they can choose activities that match their interests. The implications of these findings suggest that implementing the Merdeka Curriculum with a nature-based learning approach can serve as an effective model for early childhood education, creating an adaptive and sustainable learning environment. This approach has the potential to be applied in other early childhood education institutions to nurture children who are independent, creative, and environmentally conscious from an early age.